Effects of reaction temperature on properties of Cu2ZnSnSe4 nanoparticles. (17th May 2017) - Suzuki, Toshimasa; Suzuki, Tsukasa; Hori, Shigeo; Kawahara, Koichi; Nonomura, Shuichi
Abstract: Cu2 ZnSnSe4 (CZTSe) has been used for photovoltaic applications owing to its being a direct p-type semiconductor with reported optical band gaps of 1.0–1.5 eV and a high absorption coefficient. To clarify the effects of the reaction temperature on the optical properties of CZTSe nanoparticles (NPs), we prepared CZTSe NPs by a one-step solution process at various reaction temperatures and investigated the optical properties of the prepared NPs. CZTSe NPs with a diameter of ca. 24 nm were successfully prepared at 150–300 °C by a one-step solution process. The band gap of the prepared CZTSe NPs varied depending on the reaction temperature. The change in the band gap would be attributed to the changes in the composition and crystallinity depending on the reaction temperature.